Post-harvest processed parsnip showed improved anti-oxidative capacity and protective potential against acrolein-induced inflammation in vitro and in vivo - Lee, Kangwook; Pan, Jeong Hoon; Choi, La Yoon; Ju, Jaehyun; Le, Brandy; Williams, Liana C.; Cho, Tae Jin; Lee, Eunjin; Yoon, Ji Soo; Park, Chae Lee; Kim, Sang-Yoon; Yeon, Sung Hum; et al. (Frontiers in Nutrition, 2024)
Post-harvest processing plays a crucial role in enhancing the nutritional value and bioactive compound content of vegetables. Parsnips (Pastinaca sativa L.), root vegetables of the Apiaceae family, are rich in bioactive compounds such as polyacetylenes and furanocoumarins, known for their anti-inflammatory and antioxidant properties. This study investigated the impact of post-harvest aging on enhancing parsnip's bioactive profile and its protective effects against acrolein (Acr), an unsaturated aldehyde commonly found in cigarette smoking and burnt oil and fuel-induced respiratory inflammation in vivo. Parsnips were aged at 60°C for up to 30 days, and the resulting extracts were analyzed for total phenolic content (TPC) and DPPH radical scavenging capacity. Aging significantly enhanced both TPC (9.96-fold increase) and antioxidant capacity (4.25-fold increase), with peak values observed after 30 days. Quantitative analysis revealed increased levels of key bioactives, including falcarindiol, DDMP, and 5-HMF in aged extracts. In vitro studies demonstrated that aged parsnip extract significantly reduced Acr-induced expression of pro-inflammatory cytokines TNF-α and IL-1β. Crucially, in vivo experiments corroborated these findings, showing that Acr-exposed mice treated with aged parsnip extract exhibited reduced cytokine expression, decreased goblet cell hyperplasia, and reduced bronchial epithelial thickness. These results provide compelling evidence that post-harvest processing enhances parsnip's antioxidant and anti-inflammatory properties, effectively mitigating Acr-induced respiratory inflammation in vivo. The study highlights the potential of optimized post-harvest processing techniques to maximize parsnip's health benefits, positioning it as a promising functional food ingredient for managing oxidative stress and inflammation-related respiratory conditions.